Appearances can be Deceptive - Mukta Sharma; Rajneesh Thakur; Shalini (Delhi Journal of Ophthalmology)
Soft tissue tumors (STT) are a heterogeneous group of benign and malignant lesions. Some are assumed reactive, and others are clearly neoplastic. They can occur in skin, subcutaneous tissue, muscles, ligaments, nerves and blood vessels. These tumors vary widely in how they look and behave. More than 99% of STT are benign in nature. Here we report a case which we presumed to be lipoma but it turned out to be cavernous hemangioma.